The The Role of Drama in Improving Students' comprehension of Reported Speech - Rawend Sitorus; Chairuddin; Baihaqi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
This study aims to examine the role of drama scripts implemented through role-play activities in improving students’ comprehension of reported speech at SMK Negeri 2 Langsa. This research employed a quantitative approach using a one-group pre-test and post-test design. The population of this study consisted of all eleventh-grade students of SMK Negeri 2 Langsa, while the sample was class XI RPL comprising 25 students selected through purposive sampling. The instrument used to collect the data was a grammar test in the form of 25 multiple-choice questions focusing on reported speech. The research procedure involved administering a pre-test to measure students’ initial comprehension, followed by teaching reported speech using drama scripts through role-play activities, and finally conducting a post-test to measure students’ improvement after the treatment. The results revealed a significant improvement in students’ comprehension of reported speech. The mean score increased from 37.52 in the pre-test to 82.24 in the post-test. Furthermore, the result of the paired sample t-test showed that the significance value (Sig. 2-tailed) was 0.000, which was lower than 0.05. This indicates that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Therefore, it can be concluded that the use of drama scripts through role-play activities effectively improves students’ comprehension of reported speech. The findings imply that drama-based learning activities can be an engaging and effective strategy for teaching grammar in EFL classrooms.